2008
DOI: 10.1111/j.1750-3841.2008.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuna Pepsin: Characteristics and Its Use for Collagen Extraction from the Skin of Threadfin Bream (Nemipterus spp.)

Abstract: Pepsin from the stomach of albacore tuna, skipjack tuna, and tongol tuna was characterized. Pepsin from all tuna species showed maximal activity at pH 2.0 and 50 degrees C when hemoglobin was used as a substrate. Among the stomach extract of all species tested, that of albacore tuna showed the highest activity (40.55 units/g tissue) (P < 0.05). Substrate-Native-PAGE revealed that pepsin from albacore tuna and tongol tuna consisted of 2 isoforms, whereas pepsin from skipjack tuna had only 1 form. The activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 36 publications
7
55
1
3
Order By: Relevance
“…All treatments produced similar migration bands and contained two different main bands that corresponded to α 1 and α 2 chains derived from type I collagen, which have approximate molecular weights ranging from 120 to 130 kDa (Shin, 2002). In addition, the putative higher molecular weight band of the β chain (200 kDa) was observed in all treatments (Nalinanon et al, 2008). Thus, these results indicated that type I collagen was the major collagen type in chicken skin.…”
Section: Sds-page Analysissupporting
confidence: 49%
“…All treatments produced similar migration bands and contained two different main bands that corresponded to α 1 and α 2 chains derived from type I collagen, which have approximate molecular weights ranging from 120 to 130 kDa (Shin, 2002). In addition, the putative higher molecular weight band of the β chain (200 kDa) was observed in all treatments (Nalinanon et al, 2008). Thus, these results indicated that type I collagen was the major collagen type in chicken skin.…”
Section: Sds-page Analysissupporting
confidence: 49%
“…Fish skin can be used as an alternative source for collagen since mammalian collagens are associated with several problems such as the outbreak of mad cow disease and the constraint for some religions, mainly Islam and Judaism (Nalinanon et al 2008). Therefore, skin collagens from several fish species such as bigeye snapper (Kittiphattanabawon et al 2005;Nalinanon et al 2007), black drum (Ogawa et al 2003), brown stripe red snapper (Jongjareonrak et al 2005), carp (Duan et al 2009), channel catfish ), Nile perch (Muyonga et al 2004), oscillate puffer fish (Nagai et al 2002), sheephead seabream (Ogawa et al 2003), threadfin bream (Nalinanon et al 2008) and yellowfin tuna (Woo et al 2008) have been extracted and characterized. Although there are many reports about collagen from skin of marine organisms, there are few studies of fish scales like the studies of Kimura et al (1991) and those of Shirai (Nomura et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The main inhibitors and activators of pepsin are shown in table 2. The enzymatic activity of pepsin is almost completely inhibited by pepstatin A (aspartic proteinase competitive inhibitor that binds strongly to residues of the active site of the enzyme) and partially inhibited by phenyl methyl sulfonyl fluoride (PMSF, serinoproteinase inhibitor), L-3-carboxytrans-2, 3-epoxy-propionyl-L-leucyl-4-guanidino-butylamide (E-64), cysteine, molybdate and EDTA (Ethylenediamine tetra acetic acid, specific for metalloproteases) (DIAZ-LOPEZ et al, 1998;CASTILLO-YAÑEZ et al, 2004;TANJI et al, 2007;BOUGATEF et al, 2008;KLOMKLAO et al, 2007;NALINANON et al, 2008;NALINANON et al, 2010;WU et al, 2009;CAO et al, 2011;ZHAO et al, 2011). In contrast, the activity increases in the presence of divalent cations such as CaCl 2 , MgCl 2 and CoCl 2 (El-BELTAGY et al, 2004;KLOMKLAO et al, 2007).…”
Section: Factors Affecting the Activity (Ph Temperature Activators mentioning
confidence: 99%
“…The enzyme is also utilized in the production of fish silage, in the use of byproducts of fish processing industry and in the animal feed industry for increase protein digestibility. It is considered a promising protease with extensive industrial application of efficient effect if effective techniques for their recovery and purification can be developed (KAGEYAMA, 2002;KLOMKLAO et al, 2007;NALINANON et al, 2008;EISENMENGER & REYES-DE-CORCUERA, 2009;ZHAO et al, 2011;ZENG et al, 2012).…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation